A New Megaraptoran Dinosaur (Dinosauria, Theropoda, Megaraptoridae) from the Late Cretaceous of Patagonia - Coria, Rodolfo A.; Currie, Philip J. (PLOS ONE, 2016)
A skeleton discovered in the Upper Cretaceous Sierra Barrosa Formation (Turonian-Coniacian) of Neuquén Province, Argentina represents a new species of theropod dinosaur related to the long snouted, highly pneumatized Megaraptoridae. The holotype specimen of Murusraptor barrosaensis n.gen et n.sp. (MCF-PVPH-411) includes much of the skull, axial skeleton, pelvis and tibia. Murusraptor is unique in having several diagnostic features that include anterodorsal process of lacrimal longer than height of preorbital process, and a thick, shelf-like thickening on the lateral surface of surangular ventral to the groove between the anterior surangular foramen and the insert for the uppermost intramandibular process of the dentary. Other characteristic features of Murusraptor barrosaensis n.gen. et n. sp.include a large mandibular fenestra, distal ends of caudal neural spines laterally thickened into lateral knob-like processes, short ischia distally flattened and slightly expanded dorsoventrally. Murusraptor belongs to a Patagonian radiation of megaraptorids together with Aerosteon, Megaraptor and Orkoraptor. In spite being immature, it is a larger but more gracile animal than existing specimens of Megaraptor, and is comparable in size with Aerosteon and Orkoraptor. The controversial phylogeny of the Megaraptoridae as members of the Allosauroidea or a clade of Coelurosauria is considered analyzing two alternative data sets.